Memiilih Diantara 7 Tradisi Ilmu Komunikasi Dalam Kerangka Filosofis - Harry Setiawan (IAI Darussalam, 2019)
This article is one of many archives studies that focus on paradigms, traditions, and research in the Communication perspective from a philosophical point of view. The seventh traditions discuss in this article is owned by Robert Craig from his book titled Communication Theory, written by Littlejohn & Foss. The purpose of this research is to support the young researcher to choose and to decide which theory suite to which research paradigm that they are doing. The method is an archive study, the discussion used content analysis with the conclusion technic. The result of this research is the explanation of research based on tradition and paradigm in the Communication science field